A Study on Load Carrying Capacity of Fly Ash Based Polymer Concrete Columns Strengthened Using Double Layer GFRP Wrapping - S. Nagan; S. Karthiyaini (Advances in Materials Science and Engineering)
This paper investigates the suitability of glass fiber reinforced polymer (GFRP) sheets in strengthening of fly ash based polymer members under compression. Experimental results revealed that load carrying capacity of the confined columns increases with GFRP sheets wrapping. Altogether 18 specimens of M30 and G30 grade short columns were fabricated. The G30 specimens were prepared separately in 8 molarity and 12 molarity of sodium hydroxide concentration. Twelve specimens for low calcium fly ash based reinforced polymer concrete and six specimens of ordinary Portland cement reinforced concrete were cast. Three specimens from each molarity fly ash based reinforced polymer concrete and ordinary Portland cement reinforced concrete were wrapped with double layer of GFRP sheets. The load carrying capacity of fly ash based polymer concrete was tested and compared with control specimens. The results show increase in load carrying capacity and ductility index for all strengthened elements. The maximum increase in load carrying capacity was 68.53% and is observed in strengthened G30 specimens.